Hirohito : - Behr, Edward (Villard Books, 1989)
The late emperor Hirohito has been the subject of several biographies, notably David Bergamini's Japan's Imperial Conspiracy (LJ 12/15/71) and Leonard Mosley's Hirohito: Emperor of Japan (LJ 6/15/66). The life and times of Hirohito remain controversial, however, and there is ample need for an ongoing reassessment by responsible writers. Behr, a Newsweek correspondent, presents a well-researched (though in English-language sources only) study that provides a fascinating and probing look at the life of the 20th century's longest-reigning monarch. Behr argues that a generation of Hirohito apologists have propagated the notion that Hirohito was a "peace-loving puppet" who didn't know what his generals and ministers were up to in the 1930s and 1940s; Behr's intention is to "restore the balance." The result, however, is not "balance" but a lawyer's brief for the prosecution.